Recruitment and training policies and practices: The case of Turkey as an EU candidate - Tanova, Cem; Nadiri, Halil (My University, 2005)
Purpose - To provide information on differences between recruitment methods and training practices used in SMEs and large organizations in Turkey, as a representative of a developing country. Design/methodology/approach - A survey as designed by the Cranfield Network on International Human Resource Management (CRANET-G) was used for this study. The survey aims to obtain data that is based on facts and it does not ask for information based on respondents' opinions, attitudes or perceptions. Findings - It provides information about recruitment methods and training practices used in organizations in Turkey. It suggests that, in Turkey, small businesses are more likely to rely on employment agencies, which are considered formal recruitment sources in order to fill managerial positions, contrary to the existing literature and theoretical propositions. Additionally, with regard to training practices, it shows that large organizations use more formal training methods compared with small-and medium-sized enterprises (SMEs). Research limitations/implications - This study only includes SMEs and large organizations in Turkey as a representative of developing countries, but the findings may have implications for other developing countries. Practical implications - A very practical study which provides further insights for academics and managers of both large and small organizations. Originality/value - This paper fulfils the need of further enhancing the research in the field of HRM in developing countries, and offers practical help to individual managers operating in the same settings as Turkey. © Emerald Group Publishing Limited.
Keywords: European Union; Recruitment; Training; Turkey